Cover Image, Volume 60, Issue 12. Issue 12 (10th November 2021) - Lee, Alex J.; Fraser, Elise; Flowers, Brittany; Kim, Jee; Wong, Kenneth; Cataisson, Christophe; Liu, Huaitian; Yang, Howard; Lee, Maxwell P.; Yuspa, Stuart H.; Li, Luowei
Abstract : The cover image is based on the Research Article RAS induced senescence of skin keratinocytes is mediated through Rho‐associated protein kinase (ROCK) by Alex J. Lee et al., https://doi.org/10.1002/mc.23351 .